Клещи-краснотелки рода Odontacarus: переописание О. saxicolis Schluger, Hushcha et Kudrjaschova, 1965 (Acariformes, Leeuwenhoekiidae) - Гуща, Г.И. (Вестник зоологии, 1981)
The paper presents the redescription of Odontacarus saxicolis Schluger, Hushcha et Kudrjaschowa, 1965. The lectotype is designated from the syntypic material, collected on Lacerto saxicola from the Georgian SoR (the Caucasus).